A Discursive Institutionalist Approach to Understanding Comparative Policy Change: Ireland and Mexico in the 1980s. (December 2015) - Hogan, John; O'Rourke, Brendan K.
Abstract : Employing the critical juncture theory, a discursive institutionalist approach, this article examines the nature of changes to Irish industrial policy and to Mexican macroeconomic policy in the early 1980s. Were these significant changes, or were they continuations of previously established policy pathways? The critical juncture theory consists of three elements—economic crisis, ideational change, and the nature of the policy change—that we must identify to be able to declare with some certainty if the policy changes constituted critical junctures. Our findings will help explain why Irish industrial policy did not undergo a radical transformation during the 1980s, whereas Mexican macroeconomic policy underwent major change.